Smiljan i Koviljka Ivana Dežmana u kontekstu hrvatske romantičarske epike - Fališevac, Dunja (Array, 1996)
Smiljan and Koviljka by Ivan Dežman in the context of Croatian romantic epic poetry The paper analyses the decasyllabic epic Smiljan and Koviljka (1865) by Ivan Dežman which follows the tradition of the folk epic and Kačić's epic model, as well as other forms of folk literature such as the fable, legend, lyric poetry, joke and the anecdote. On the other hand Dežman's epic is based on the tradition of the Romantic-chivalric epic, of Arioste, Tasso and Gundulić. Thus it creates a structure that is expressly fictional, entertaining, full of adventures and miraculous events, forming a naive, ludic and stylised epic structure in accordance with the Romantic concept of the literay tekxt as a work that shapes folk tradition and the spirit of the people.